Digital human modeling : applications in health, safety, ergonomics, and risk management : 9th International Conference, DHM 2018, held as part of HCI International 2018, Las Vegas, NV, USA, July 15-20, 2018, Proceedings /: applications in health, safety, ergonomics, and risk management : 9th International Conference, DHM 2018, held as part of HCI International 2018, Las Vegas, NV, USA, July 15-20, 2018, Proceedings. (2018) - Unknown
No abstract available